2008
DOI: 10.2337/dc07-2184
|View full text |Cite
|
Sign up to set email alerts
|

Liver Enzymes Compared With Alcohol Consumption in Predicting the Risk of Type 2 Diabetes

Abstract: OBJECTIVE -It has been reported that moderate alcohol consumption decreased the risk of type 2 diabetes but that elevated liver enzymes increased it. The comparative importance of alcohol consumption and liver enzymes as predictors of type 2 diabetes remains unconfirmed.RESEARCH DESIGN AND METHODS -The participants included 8,576 Japanese men, aged 40 -55 years, without type 2 diabetes at entry. Type 2 diabetes was diagnosed if a fasting plasma glucose level was Ն126 mg/dl or if participants were taking oral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 23 publications
4
55
2
1
Order By: Relevance
“…Recent prospective studies have confirmed a significant association between GGT activity and the incidence of type 2 diabetes in both sexes and in various populations, including the DESIR cohort [12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Recent prospective studies have confirmed a significant association between GGT activity and the incidence of type 2 diabetes in both sexes and in various populations, including the DESIR cohort [12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that serum GGT is a biomarker of increased alcohol consumption [1][2][3][4]22) ; however, GGT is known to be affected by other con- 23,24) . Evidence is accumulating that higher serum GGT levels may be associated with an increased incidence of cardiovascular events 5) , metabolic syndrome and diabetes 8,25,26) ; therefore, more attention has been paid recently to this liver enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the study have been described previously (18,19). Between April 2000 and March 2001, 12,647 male employees of a company in the area of Kansai, Japan, aged 40 to 55 years at entry and considered to be involved in sedentary jobs, were enrolled in this study.…”
Section: Site and Settingmentioning
confidence: 99%